Psychological Resilience of Second-Pregnancy Women in China: A Cross-sectional Study of Influencing Factors - Xiaohuan Jin; Xinyuan Xu; Junyan Qiu; Zexun Xu; Lixue Sun; Zhilin Wang; Ling Shan (Elsevier, 2021)
Purpose: The aim of the study was to evaluate the status of psychological resilience among women in their second pregnancy and to investigate the possible influencing factors. Methods: A total of 275 women in their second pregnancy and who met the criteria were surveyed from two public hospitals in China from July 2018 to January 2019. The instruments included the General Self-designed Questionnaire, Connor-Davidson Resilience Scale, Social Support Rate Scale, and 36-item Pregnancy Stress Rating Scale. Results: The total psychological resilience score of second-pregnancy women was relatively low. Multivariate regression analysis identified five factors associated with psychological resilience: intimacy with husbands, social support utilization, gender of the first child, high-risk pregnancy of the first child, and the stress caused by worrying about the health and safety of the mother and fetus. Conclusion: Women in their second pregnancy represent a unique population, and their low psychological resilience score deserves attention. Identification of factors contributing to decreased psychological resilience may enable us to design prevention and intervention strategies and to deliver specific psychological supports to pregnant women at high risk of developing negative psychology.